After-fracture redundancy analysis of an aged truss bridge in Japan. Issue 1 (2nd January 2017) - Lin, Weiwei; Lam, Heang; Yoda, Teruhiko; Ge, Haijie; Xu, Ying; Kasano, Hideyuki; Nogami, Kuniei; Murakoshi, Jun
Abstract: In the next 20 years, more than half of the bridges in Japan would be in service for more than 50 years. These include truss bridges those are generally considered to be non-redundant and fracture critical. With ageing, these bridges are facing an increasing risk of bridge collapse under extreme conditions. Therefore, it is essential to evaluate alternate load paths on existing bridge structures to avoid bridge collapse or replacement. In this paper, after-fracture redundancy of truss bridges is investigated through a case study for a five-span continuous truss bridge. Field tests were performed, and the displacements on key sections were measured in the test. According to the experimental observations and test results, a numerical model capable of simulating the present truss bridge was built and was used to investigate the after-fracture redundancy of the target bridge. Fracture of truss members in typical locations was considered in the numerical analyses, and the 'R' values of both intact and damaged trusses were compared. On the basis of the numerical results, a critical member in this bridge was also determined.